Study on the Structural Design and Obstacle Barrier Performance of Double Pendulum Arms Crawler Deformable Robot - Guangyao Meng; Zhenhua Wang; Juxin Huang; Bin Guo; Hongjie Sun (Jixie chuandong)
In order to make the best obstacle performance of the crawler deformable robot, and to ensure that the crawler length does not change and continue to tension during the change process, the ellipse theorem and the elliptical rule principle are applied to the robot configuration design, and a new type of crawler deformable robot is developed. The introduction of the rear swing arm enriches the configuration change of the robot, and the center of gravity of the robot has a large degree of adjustment during the rotation of the front and rear swing arms, the obstacle performance of the robot is improved. Mathematical models of typical obstacles such as ramps, steps and gullies are established. The gait planning and motion mechanism analysis of robot overcoming obstacles are established. The kinematics and dynamics models of robot obstacles are established, and the critical conditions for robots to overcome various obstacles are analyzed. The limit value is simulated by Adams to overcome the obstacles, and the accuracy of the theoretical calculation value and the obstacle performance of the robot are verified.